2023
DOI: 10.26434/chemrxiv-2023-l3knn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wall-slip effects on the Yield-stress fluid flows in the rigid and deformable channel

Ashish Garg,
Pranjal Prasad

Abstract: Yield stress fluids flow through deformable conduits and are prevalent in nature and have numerous technological applications [1-11]. In this paper, we focus on investigating the impact of many factors such as the deformability of the channel-wall, yield stress, shear-thinning, and shear-thickening index in the presence of slip and compared it with flow dynamics with no-slips as predicted by Garg and Prasad [12]. Using lubrication theory, we have derived a model for the velocity profiles and flow rate using th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…The results gathered from these simulations collectively support the idea that even in highly narrow CNTs with a diameter as small as 1.66 nm, the flow of water behaves following the slip-modified Hagen-Poiseuille relation. Interestingly, the actual flow rates they observed were higher than what we would expect based on the traditional no-slip Hagen-Poiseuille relation [29][30][31], where water sticks to the tube walls. However, their theory failed to support the claims made by Majumder et al [15] and Holt [32,33] in their previous studies, where they suggested that water behaves very differently in these nanotubes.…”
Section: Introductionmentioning
confidence: 81%
“…The results gathered from these simulations collectively support the idea that even in highly narrow CNTs with a diameter as small as 1.66 nm, the flow of water behaves following the slip-modified Hagen-Poiseuille relation. Interestingly, the actual flow rates they observed were higher than what we would expect based on the traditional no-slip Hagen-Poiseuille relation [29][30][31], where water sticks to the tube walls. However, their theory failed to support the claims made by Majumder et al [15] and Holt [32,33] in their previous studies, where they suggested that water behaves very differently in these nanotubes.…”
Section: Introductionmentioning
confidence: 81%
“…The results gathered from these simulations collectively support the idea that even in highly narrow CNTs with a diameter as small as 1.66 nm, the flow of water behaves following the slip-modified Hagen-Poiseuille relation. Interestingly, the actual flow rates they observed were higher than what we would expect based on the traditional no-slip Hagen-Poiseuille relation [29][30][31], where water sticks to the tube walls. However, their theory failed to support the claims made by Majumder et al [15] and Holt [32,33] in their previous studies, where they suggested that water behaves very differently in these nanotubes.…”
Section: Introductionmentioning
confidence: 81%
“…Their MD simulations consistently support the notion that water flow within nanochannels adheres to the slip-modified Hagen-Poiseuille relation. This finding is particularly interesting because it suggests higher flow rates compared to those predicted by the traditional no-slip Hagen-Poiseuille relation [16][17][18], which assumes water molecules stick to the channel walls. Also, Israelachvili [13] experimentally calculated the viscosity of tetradecane and water between two mica sheets placed at distances lower than 50 Å and proposed that the viscosity of water/tetradecane can be calculated using…”
Section: Introductionmentioning
confidence: 84%